Heterogeneous Preferences for Domestic Fresh Produce: Evidence from German and Italian Early Potato Markets. Issue 4 (1st March 2016) - Colantuoni, Francesca; Cicia, Gianni; Del Giudice, Teresa; Lass, Daniel; Caracciolo, Francesco; Lombardi, Pasquale
ABSTRACT: In this research, we explore the market potential of a domestic agricultural product, the early potato, in two countries, Italy and Germany. We conducted two parallel marketing studies aimed at revealing the most desirable characteristics for the commercialization of this product in each of the two markets, and made comparisons among consumers' attitudes for several attributes (country of origin, carbon footprint, production method, ethical certification and packaging). Motivation for this study is the declining market share of the domestic early potato, considered an important crop in both countries, due to the competition from abroad. A focal aspect of this research is the recent public interest for social justice, traditionally reserved for products imported from developing countries, with respect to ethical products made in developed countries. The possibility for Italian and German early potatoes to regain important market shares depends on the ability to differentiate their potatoes from potatoes supplied by competing extra‐European countries. [JEL Classifications: Q13; Q18].